Questions About the Protection of Corrosion Inhibitors of Equipment and Pipelines in the Oil and Gas Industry - K. P. Norbutaeva (Genius Journals, 2022)
The gas industry is associated with the consumption of a huge amount of metal, which by its nature is subject to corrosion. Corrosion occurs in preparation for gas production, in the process of its processing and transportation. Especially intensively corrodes metal equipment during gas production, because. natural gas contains such aggressive metal components as hydrogen sulfide, carbon dioxide, water vapor and organic acids. The article deals with the issues of inhibitor protection of oil and gas equipment from corrosion.
Keywords: gas and oil pipelines; inhibitor protection; volatile inhibitors